ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLES ON FIXED RETAINER ADHESIVE TOWARD TREPONEMA DENTICOLA - SANTOSO, JESSICA; PURBIATI, MARIA; KRISNAWATI (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to develop an antibacterial flowable composite containing silver nanoparticle (AgNP) for the prevention of periodontal disease in fixed retainers. Methods: About 1% AgNP was incorporated into a commercial composite (tetric flow). The experimental and control products were used to bond fixed retainers to 28 extracted mandibular first premolars. The samples were randomly divided into four groups (n=7): Premolar bonded with fiber-reinforced composites and tetric flow (F1); premolar bonded with fiber-reinforced composites and AgNP-enhanced tetric flow (F2); premolar bonded with multistranded wires (MW) and tetric flow (M1); and premolar bonded with MW and AgNP-enhanced tetric flow (M2). Each sample was submerged in a test tube containing bacterial Treponema denticola solution and was incubated for 24 h and 37°temperature. The bacterial colony in each group was counted and analyzed. Results: This study showed that there was significant difference of T. denticola colony count between groups with and without AgNP-enhanced composites in both types of retainers. Conclusion: AgNP-enhanced flowable composites reduce the bacteria T. denticola colony count and possibly inhibit periodontal disease.